Comparison of Laparoscopic and Open Appendectomy in Terms of Surgical Site Infection - Shahid Hussain Mirani, Muhammad Tahir Ali, Dileep Kumar, Khalid Abaidullah, Abdul Rasheed Zai, Muhammad Hanif Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the laparoscopic and open appendectomy in terms of surgical site infection. Study Design: Retrospective study Place and Duration of Study: Department of Surgery Unit-2, Ghulam Muhammad Mahar Medical College Hospital Sukkur from 1st January 2019 to 31st December 2020. Methodology: One hundred patients who were further divided in two groups with 50 patients each were enrolled after clinical confirmation of appendicitis. Group A was operated through open surgery method while Group B was operated laparoscopically. The data regarding hospital stay, duration of surgery and surgical site infection through both techniques was compared and data analyzed. Results: The mean age of patients was 26.5±5.5 years males with a percentage of 76% where as only 24% of the study cases were females. Patients undergoing laparoscopy were having reduced prevalence of surgical site infection as 10% than who underwent open surgery. Among the 26.54% of reported co-morbidity cases as well, there were 65% those who has surgical site infection with open surgery protocol. Conclusion: Laparoscopic surgery technique is highly efficient in reducing surgical site infection in comparison to open surgery method.